MINAT BELAJAR PAI DALAM EKSPERIMEN MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING (CPS) BERBASIS MEDIA TEKNOLOGI (ICT) - Risqi Mulyasari; Imam Syafei; Listiyani Siti Romlah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning interest is a crucial factor influencing the effectiveness and success of the learning process, as it affects students’ attention, engagement, and motivation during classroom activities. Preliminary observations at SMP Muhammadiyah 3 Bandar Lampung indicated that students’ learning interest in Islamic Religious Education (PAI) was relatively low, particularly in attention and interest, due to monotonous teaching methods and limited use of technology. Therefore, this study aimed to examine the effect of the Creative Problem Solving (CPS) learning model supported by Information and Communication Technology (ICT) on students’ learning interest in PAI. This research employed a quantitative approach using a quasi-experimental method with a post-test only control group design. The sample was selected through simple random sampling, involving class VII.D as the experimental group and class VII.F as the control group. Data were collected using a non-test questionnaire based on two indicators of learning interest, namely attention and interest. Instrument validity and reliability were tested using Pearson correlation and Cronbach’s Alpha. Prior to hypothesis testing, data were analyzed using normality and homogeneity tests, followed by an independent samples t-test. The results showed that the ICT-based CPS learning model had a statistically significant effect on students’ learning interest, with a significance value of 0.009 (p < 0.05). Students in the experimental group demonstrated higher levels of attention and interest than those in the control group. These findings indicate that the CPS learning model supported by technology-based media is an effective strategy for enhancing students’ learning interest in Islamic Religious Education in schools.